Snapping at the Lateral Aspect of the Elbow: A Case Report and Review of the Literature. Issue 3 (July 2018) - Feller, Ross J.; Gil, Joseph A.; DaSilva, Manuel
Abstract : Case: A 59-year-old man presented with snapping at the lateral aspect of the elbow and associated pain. Magnetic resonance imaging demonstrated extensor tendinopathy and thickening of the radial collateral ligament. Ultrasonography showed entrapment of a synovial fold in the radiohumeral joint. Initial arthroscopic debridement did not alleviate the snapping. Three months later, the patient underwent open excision of a thickened and partially torn annular ligament; subsequently, all of the symptoms resolved. Conclusion: Snapping elbow is a phenomenon that often coincides with pain and limited function. Accurate diagnosis is critical because misdiagnosis has been demonstrated to have serious consequences, including the need for repeat surgery.